Centrioles, centrosomes, and cilia in health and disease. - Nigg, E; Raff, J (2009)
Centrioles are barrel-shaped structures that are essential for the formation of centrosomes, cilia, and flagella. Here we review recent advances in our understanding of the function and biogenesis of these organelles, and we emphasize their connection to human disease. Deregulation of centrosome numbers has long been proposed to contribute to genome instability and tumor formation, whereas mutations in centrosomal proteins have recently been genetically linked to microcephaly and dwarfism. Finally, structural or functional centriole aberrations contribute to ciliopathies, a variety of complex diseases that stem from the absence or dysfunction of cilia.